The Impact of Tetracycline Pollution on the Aquatic Environment and Removal Strategies - Yernar Amangelsin; Yuliya Semenova; Maryam Dadar; Mohamad Aljofan; Geir Bjørklund (MDPI AG, 2023)
Antibacterial drugs are among the most commonly used medications in the world. Tetracycline is a widely used antibiotic for human and animal therapy due to its broad-spectrum activity, high effectiveness, and reasonable cost. The indications for treatment with tetracycline include pneumonia, bone and joint infections, infectious disorders of the skin, sexually transmitted and gastrointestinal infections. However, tetracycline has become a serious threat to the environment because of its overuse by humans and veterinarians and weak ability to degrade. Tetracycline is capable of accumulating along the food chain, causing toxicity to the microbial community, encouraging the development and spread of antibiotic resistance, creating threats to drinking and irrigation water, and disrupting microbial flora in the human intestine. It is essential to address the negative impact of tetracycline on the environment, as it causes ecological imbalance. Ineffective wastewater systems are among the main reasons for the increased antibiotic concentrations in aquatic sources. It is possible to degrade tetracycline by breaking it down into small molecules with less harmful or nonhazardous effects. A range of methods for physical, chemical, and biological degradation exists. The review will discuss the negative effects of tetracycline consumption on the aquatic environment and describe available removal methods.